Fire prediction monitoring system based on a spatial interpolation algorithm - Karrar Shakir Muttair; Ali Zuhair Ghazi Zahid; Rana Jawad Azeez; Oras Ahmed Shareef Al-Ani; Ahmed Mahmood Farhan; Raed Hameed Chyad Alfilh; Raed Hasan Hussain; Muthana H. Al-Saidi; Abbas Ali Diwan; Zeshan Ahmed; Hazeem Baqir Taher (International Journal of Reconfigurable and Embedded Systems (IJRES), 2026)
Fires endanger not only the environment's wealth but also the entire fauna and flora, drastically disrupting a region's biodiversity and ecology. This article monitors the spread of a fire in a specific area, determines its approximate direction, attempts to extinguish it in an organized manner, and identifies the safest solutions. A new system has been developed, consisting of two parts: embedded and reconfigurable. This system comprises four accurate flame sensors, a buzzer, an Arduino, and a field-programmable gate array (FPGA) DEV board. The Arduino and FPGA collect data from these sensors and send it to MATLAB, which processes and displays the results. This paper also uses a two-stage prediction based on a spatial interpolation algorithm. The results showed that the speed and direction of fire spread could be predicted quickly and accurately using a spatial interpolation algorithm, achieving the lowest predictive error (mean absolute error (MAE) ≈0.33 and root mean square error (RMSE) ≈0.48) at approximately epoch 70. Moreover, the proposed method achieved a 92% success rate in detecting flames and fire flashes, indicating that the sensors respond to fires within under 1 minute of occurrence.